2002
DOI: 10.1152/ajpcell.00341.2002
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of stretch-induced loss of alveolar epithelial barrier integrity with a novel in vitro method

Abstract: Mechanical ventilation with high tidal volumes has been shown to contribute to the formation or worsening of interstitial and alveolar edema. Previously we showed that application of large biaxial deformations in vitro perturbs the concentration and distribution of functional tight junction proteins in alveolar epithelial cells. Using a novel method, we determined that applied epithelial strain increases paracellular permeability in a dose- and rate-dependent manner. Primary rat alveolar epithelial cells were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
53
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 24 publications
5
53
0
Order By: Relevance
“…Although data exist indicating that the transport of molecules >30 Å in radius across the alveolar epithelium may occur via endocytosis or other active processes (33), the similarities between the monolayers and whole lung results support the extrapolation of our in vitro data to the in vivo milieu. The applicability of our monolayer data to the in vivo setting is further supported by our previous finding that stretch of cultured alveolar epithelial cells at 37% ΔSA increased the paracellular permeability of the monolayer to a ouabain derivative ~20 Å in radius (6). Finally, we only employed tracers with a neutral net charge.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Although data exist indicating that the transport of molecules >30 Å in radius across the alveolar epithelium may occur via endocytosis or other active processes (33), the similarities between the monolayers and whole lung results support the extrapolation of our in vitro data to the in vivo milieu. The applicability of our monolayer data to the in vivo setting is further supported by our previous finding that stretch of cultured alveolar epithelial cells at 37% ΔSA increased the paracellular permeability of the monolayer to a ouabain derivative ~20 Å in radius (6). Finally, we only employed tracers with a neutral net charge.…”
Section: Discussionsupporting
confidence: 54%
“…This threshold stretch magnitude is the same level that we reported previously to disrupt tight junction structure and barrier function in similarly cultured cells (6,7), although barrier properties were assessed using a single larger tracer (radius = 15-20 Å). Tight junction properties in these two studies also were not affected by lower magnitudes of stretch, similar to what was observed in the current preparation.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Furthermore, TJ have previously been reported to respond to mechanical tension as alterations in TJ strand arrangement and orientation occur when MEC are stretched in vitro [42]. In lung alveolar epithelial cells increased TJ permeability occurs during cyclic stretch [21,43,44]. The latter was associated with a decline in abundance of occludin protein, but no differences were detected in ZO-1 protein [21].…”
Section: Discussionmentioning
confidence: 99%